Component Analysis and Antibacterial Effect of Star Anise Essential Oil - Ji Yihe; Lemiasheuski Viktar (BIO Web of Conferences)
Star anise essential oil has shown a wide range of application prospects in the fields of food, medicine and health products due to its potential biological activity. This paper reviews the extraction method and chemical composition of star anise essential oil, and discusses its antibacterial effect. Coriander seeds selected from China were used to extract coriander essential oil by distillation extraction, and its compound components were qualitatively and quantitatively analyzed by gas chromatography-mass spectrometry (GC-MS), and the main components were evaluated by Fourier transform infrared spectroscopy (FTIR). The main component was detected to be anethole, with a content of 80%~90%. In addition, there was a small amount of anisaldehyde. Antibacterial experiments were carried out on selected opportunistic microorganisms, and it was found that star anise essential oil had significant effects on Staphylococcus aureus, Escherichia coli, Bacillus cereus, and Proteus.